2005
DOI: 10.1161/circulationaha.104.525733
|View full text |Cite
|
Sign up to set email alerts
|

Large Area of the False Lumen Favors Secondary Dilatation of the Aorta After Acute Type A Aortic Dissection

Abstract: Background— Since 1994 patients with acute aortic dissection type A (AADA) are followed-up in our outpatient clinic. Early diagnosis of secondary dilatation of the diseased aorta is crucial to reduce late mortality in these patients. Aim of the present study is to asses the impact of a large volume in the false lumen of the diseased downstream aorta on secondary dilatation. Methods and Results— 134 patients of 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Other variables have been considered to have poor prognosis, such as compression of the true lumen 61 or partial false lumen thrombosis. 62 In contrast, a completely thrombosed false lumen showed a protective role.…”
Section: Acute Aortic Syndrome Prognosis and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Other variables have been considered to have poor prognosis, such as compression of the true lumen 61 or partial false lumen thrombosis. 62 In contrast, a completely thrombosed false lumen showed a protective role.…”
Section: Acute Aortic Syndrome Prognosis and Follow-upmentioning
confidence: 99%
“…63 In addition to maximal aortic diameter, some TOE information such as echolucent areas has been related to dissection and enlargement evolution. 61 The natural history of PAU is unknown. Like intramural haematomas, several evolutive possibilities have been proposed.…”
Section: Acute Aortic Syndrome Prognosis and Follow-upmentioning
confidence: 99%
“…Immer and colleagues 16 reported that a large false lumen with an area of the true lumen < 30% 6 months after surgery is the strongest predictor for secondary dilatation of the diseased downstream aorta. This finding is consistent with the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a FL diameter larger than 22 mm is predictive of an aneurysm with a sensitivity of 100% and specificity of 76%. Even though the true lumen diameter can change with blood pressure and cardiac cycle, it is still an important predictor of blood support to vital organs and tissues ( 36 , 37 ). Moreover, complete FLT is the ultimate goal of treatment since it indicates a good prognosis ( 11 ).…”
Section: Discussionmentioning
confidence: 99%